Time-To-Thunder Method Of Lightning Distance Determination - Wan Ismail, Ibrahim (2010)
Abstract—The lightning strike hazards may be properly managed by using a lightning detector system. In this paper, a system to determine the lightning strike distance from the measuring point was developed and tested. The time-tothunder method was used to determine the strike distance. The technique was implemented using two kinds of sensors, namely, a broadband antenna to detect the electric field, and a microphone to detect the acoustic signal produced when lightning strike to the ground. A simple procedure to find the strike distance (d) was explained. A broadband parallel plate antenna was used to detect the electric field signal. The acoustic signal was detected by a microphone. The arrival time-delay between both signals was used to calculate the strike distance. The LabVIEW 8.5 software was used as a data logger to calculate the distance and to save the data. The lightning distance data were recorded for duration from January 2010 until March 2010 using the developed system. The range of the lightning detection is up to 10 km in radius.